Neutrophil extracellular traps and interleukin-1β in cystic fibrosis lung disease - Fantone, Kayla M.; Gokanapudi, Naveen; Rada, Balázs (Frontiers in Immunology, 2025)
Cystic fibrosis (CF) lung disease manifests through abnormally thick mucus, persistent bacterial infections and a dysregulated innate immune system that involves significant neutrophilic inflammation. Neutrophils, immune cells essential to fight infections, accumulate in large numbers in CF airways and release neutrophil extracellular traps (NETs) into the airway lumen that deliver extracellular DNA, granule content and cytokines including IL-1β. Interleukin-1β, a powerful, proinflammatory cytokine, represents another, significant component of the innate immune system that is dysregulated in CF. Both defense mechanisms become problematic as NETs and IL-1β are present at elevated levels in CF airways, potentially creating a destructive cycle that exacerbates lung damage rather than protects against infections. Therefore, understanding the interplay between IL-1β and NETs is crucial for addressing CF lung disease progression. This review examines the general mechanisms of IL-1β release and NET formation, with particular focus on their role in CF lung disease, and proposes that a self-perpetuating, positive feedback loop between these two innate immune processes represents a major driving force in disease progression. This understanding suggests potential therapeutic targets for interrupting the cycle of inflammation and tissue damage in CF airways.